PENGARUH KEPEMIMPINAN, KOMPENSASI, DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN PENJUALAN PADA PT AGUNG AUTOMALL SM. AMIN PEKANBARU - Manalu Halomoan Dendi; Marzolina Marzolina; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Leadership (X1), Compensation (X2),and Workload (X3) on Job Satisfaction (Y) employees of the sales division at PTAgung Automall SM. Amin Pekanbaru. The population of study included allemployees of the sales division at PT Agung Automall SM. Amin Pekanbar was 35people and the sampling technique was saturation sampling. Primary wascollected by questionnaire as an instrument to prove the result of research. Linearregression analysis used as methods of data analysis. The results were: 1)Leadership had positive and significant effect on Job Satisfaction employees ofthe sales division at PT Agung Automall SM. Amin Pekanbaru; 2) Compensationhad positive and significant effect on Job Satisfaction employees of the salesdivision at PT Agung Automall SM. Amin Pekanbaru; 3) Workload had negativebut not significant effect on Job Satisfaction employees of the sales division at PTAgung Automall SM. Amin Pekanbaru; 4) Leadership Compensation, andWorkload simultaneously effect on Job Satisfaction employees of the salesdivision at PT Agung Automall SM. Amin Pekanbaru. Keyword: Leadership, Compensation, Workload, Job Satisfaction